Cerebrospinal Fluid Aβ43 Is Reduced in Early-Onset Compared to Late-Onset Alzheimer’s Disease, But Has Similar Diagnostic Accuracy to Aβ42 - Lauridsen, Camilla; Sando, Sigrid B.; Møller, Ina; Berge, Guro; Pomary, Precious K.; Grøntvedt, Gøril R.; Salvesen, Øyvind; Bråthen, Geir; White, Linda R. (Frontiers in Aging Neuroscience, 2017)
Background Amyloid beta 1-43 (Aβ43) may be a useful additional biomarker for diagnosing Alzheimer’s disease (AD). We have investigated cerebrospinal fluid (CSF) levels of Aβ43 in patients with early-onset AD in contrast to levels in late-onset AD. For comparison, in addition to the ‘core’ biomarkers, several other analytes were also determined (YKL-40, neurofilament light (NF-L), glial fibrillary acidic protein (GFAP), and progranulin). Material and Methods CSF samples were obtained from patients with early-onset AD (age≤62, n=66), late-onset AD (age≥68, n=25), and groups of cognitively intact individuals (age≤62, n=41, age≥68, n=39). Core CSF AD biomarkers (amyloid beta 1-42 (Aβ42), total tau, phosphorylated tau) were analyzed, as well as levels of Aβ43 and other analytes, using commercially-available enzyme-linked immunosorbent assays. Results CSF Aβ43 was significantly reduced in early-onset AD compared to late-onset AD (14.8 ± 7.3 vs. 21.8 ± 9.4 pg/ml respectively), whereas the levels of Aβ42 in the two AD groups were not significantly different (474.9 ± 142.0 vs. 539.6 ± 159.9 pg/ml respectively). Aβ43 and all core biomarkers were significantly altered in patients with AD compared to corresponding controls. NF-L was significantly increased in early-onset AD compared to younger controls, an effect not found between the older groups. Relationships between the Aβ peptides and tau proteins, YKL-40, NF-L, GFAP and progranulin were also investigated without finding marked associations. However, age-associated increases in levels of tau proteins, YKL-40, NF-L and GFAP were found with respect to age in healthy controls. Results for these other analytes were similar to previously published data. Aβ43 did not improve diagnostic accuracy in either AD group compared to Aβ42. Discussion CSF Aβ43, but not Aβ42 levels, varied significantly with age in patients with AD. If CSF levels of Aβ peptides reflect amyloid deposition in brain, the possibility arises that there is a difference between Aβ43 and Aβ42 deposition in younger compared to older brain. However, the level of Aβ43 in CSF shows no improvement over Aβ42 regarding diagnostic accuracy.